Assessing suicide risk in patients with heart failure: a systematic review and meta-analysis - Zeng, Yujia (Frontiers in Psychiatry, 2025)
BackgroundHeart failure (HF) is a long-lasting and challenging condition. It often relates to issues with mental health and suicidal behavior. However, the exact level of suicide risk in HF patients is not well understood. This systematic review and meta-analysis aimed to assess the connection between HF and suicide risk in adults.MethodsPubMed, Scopus, and Web of Science were searched up to June 2025. The emphasis was on research that presented outcomes related to suicide in patients with heart failure. Included studies featured adults who were 18 years of age or older and reporting quantitative information, like odds ratios, about suicidal ideation, attempts, or completions. To explore heterogeneity, subgroup analyses were performed based on diagnostic criteria for suicidal behaviors (ICD-9 versus ICD-10) and study design.ResultsOut of 1,643 records, 8 studies were eligible based on the criteria described. The pooled analysis showed a significantly higher risk of suicide in HF patients compared to the general population with no major cardiovascular diseases (OR = 1.62, 95% CI: 1.49-1.74) compared to healthy subjects, with substantial variability (I² = 88.23%). Subgroup analyses revealed that studies using ICD-9 criteria (OR = 1.75, 95% CI: 1.65–1.85) and case-control designs (OR = 1.75, 95% CI: 1.66–1.83) had significantly higher pooled suicide risk estimates than studies using ICD-10 criteria (OR = 1.46, 95% CI: 1.38–1.54) and cohort designs (OR = 1.46, 95% CI: 1.38–1.54). Furthermore, between-group differences were statistically significant (Q = 20.05 and 23.49, p < 0.001), suggesting that diagnostic criteria and study design were significant sources of heterogeneity.ConclusionHF is connected to a significantly higher risk of suicide. These results emphasize the importance of regular mental health check-ups and early support in HF care, especially shortly after diagnosis.